2019
DOI: 10.1186/s13059-018-1604-0
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-196a derived from cancer-associated fibroblasts confers cisplatin resistance in head and neck cancer through targeting CDKN1B and ING5

Abstract: BackgroundCisplatin resistance is a major challenge for advanced head and neck cancer (HNC). Understanding the underlying mechanisms and developing effective strategies against cisplatin resistance are highly desired in the clinic. However, how tumor stroma modulates HNC growth and chemoresistance is unclear.ResultsWe show that cancer-associated fibroblasts (CAFs) are intrinsically resistant to cisplatin and have an active role in regulating HNC cell survival and proliferation by delivering functional miR-196a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
306
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(312 citation statements)
references
References 53 publications
6
306
0
Order By: Relevance
“…Furthermore, our data also demonstrated that TGF-β1-containing CSC_EVs possibly participate in the transformation of NGFs into CAFs and might promote their metastatic potential, thereby transforming the TME. This is in part consistent with previous evidence that CAF-secreted EVs facilitate the tumorigenesis of oral cancer cells [36][37][38]. However, the observation that CSC_EVs promoted the transformation of NGFs to CAFs is unique to this study and is the first such documentation, to the best of our knowledge.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, our data also demonstrated that TGF-β1-containing CSC_EVs possibly participate in the transformation of NGFs into CAFs and might promote their metastatic potential, thereby transforming the TME. This is in part consistent with previous evidence that CAF-secreted EVs facilitate the tumorigenesis of oral cancer cells [36][37][38]. However, the observation that CSC_EVs promoted the transformation of NGFs to CAFs is unique to this study and is the first such documentation, to the best of our knowledge.…”
Section: Discussionsupporting
confidence: 92%
“…Emerging evidence demonstrates that non-malignant CAFs can contribute to tumor proliferation, metastasis, and chemoresistance. CAFs secrete specific cytokines, proteins, or exosomal miRNA to activate certain anti-apoptosis related signaling pathways like PI3K/Akt, ANXA3/JNK, and IL-11/IL-11R/STAT3, and consequently offer tumor cells the ability of resistance (Tao et al, 2016;Zhou et al, 2016a;Zheng et al, 2017b;Qin et al, 2019;Wang et al, 2019b). CAFs can also cause the aberrant remodeling of extracellular material and physical properties of the tumor altered, or release cysteine and GSH to limit the intracellular platinum concentration (Akkari and Joyce, 2016;Wang et al, 2016b).…”
Section: Cafsmentioning
confidence: 99%
“…By targeting cyclin-dependent kinase inhibitor 1B (CDKN1B) and inhibitor of growth family member 5 (ING5), miR-196a-5p facilitates cell growth and inhibits cell death, respectively. Therefore, exosomal miR-196a-5p ultimately serves as the deteriorating factor of cisplatin resistance [179] (Figure 3).…”
Section: Mir-196a-5pmentioning
confidence: 99%